COMMUNITY INVOLVEMENT AND SOCIAL EMPOWERMENT IN TOURISM DEVELOPMENT - Rachmawati, Dr Eva; Hidayati, Syafitri; Rahayuningsih, Tri (Media Konservasi, 2022)
Scholars has emphasized that community involvement are an important factor in achieving sustainable tourism goals, including community empowerment. The study purpose is to identify community perception of social empowerment resulted from tourism development, to analyze the community involvement in tourism development and to analyze the relationship between community involvement and perceptions related to social empowerment in tourism development. The method employ in this research was a quantitative approach (i.e., household survey). The result showed that majority respondents have a positive perception related social empowerment indicators, including conflict in the area. Community involvement in tourism industry and decision-making process could enhance respondents’ perceptions toward social empowerment indicators. It can be seen from the percentage of the respondents who has positive perception is higher than those who do not involve in tourism industry or decision-making process. The interesting finding is, however, despite the limited resources due to island condition and the ethnic composition that dominate by certain ethnic group, the conflict occurs in the area seems to be low. Since more respondent are disagree if tourism in their area increase the conflict. Key words: community involvement, decision-making process, tourism industry